Association between admission baseline blood potassium levels and all-cause mortality in patients with acute kidney injury combined with sepsis: A retrospective cohort study. - Yifan Guo; Yue Qiu; Taiqi Xue; Pu Yan; Wenjing Zhao; Mengdi Wang; Cheng Liu; Ning Zhang (PLoS ONE)
Introduction Imbalances in blood potassium (K) homeostasis is a significant contributor to the emergence of severe complications, especially among critically ill patients. Hypokalemia and hyperkalemia are both associated with an increased risk of adverse events. However, it is not known about the impact of blood K levels on risk of intensive care units (ICU) mortality for Acute kidney injury (AKI) combined with sepsis patients. This study aimed to explore the relationship between admission blood K levels and ICU 30-day mortality in patients with AKI combined with sepsis. Methods We selected patients diagnosed with AKI and sepsis on their first ICU admission from the Medical Information Mart for Intensive Care IV (MIMIC-IV) database. The first blood K levels within 24 hours of admission were categorized into three groups according to tertiles (T1 < 3.9 mmol/L, 3.9 ≤ T2 < 4.5 mmol/L, and T3 ≥ 4.5 mmol/L), with T2 serving as the reference. We examined the association between blood K levels and ICU 30-day mortality using accelerated failure time (AFT) models and survival analysis. Results A total of 8,242 ICU patients with AKI combined with sepsis were included. In multivariate AFT models, each 1 mmol/L increase in blood K levels was associated with a 13% increase in the risk of ICU 30-day mortality (p < 0.001, 95% confidence interval (CI): 1.06-1.20). Extended multivariable AFT models showed that, compared to the middle category, patients with high blood K levels (≥ 4.5 mmol/L) were associated with all-cause mortality (p = 0.002, adjusted hazard ratio (HR) = 1.22, 95% CI: 1.08-1.38), whereas those with low blood K levels (< 3.9 mmol/L) showed no significant difference (p = 0.385, adjusted HR = 1.06, 95% CI: 0.93-1.21). Kaplan-Meier curves indicated that patients with high blood K levels had higher mortality, and those with middle blood potassium levels (3.9 ≤ K < 4.5 mmol/L) had the lowest mortality. Conclusion The admission baseline blood K levels were significantly associated with ICU 30-day mortality in intensive care patients suffering from AKI in conjunction with sepsis. Therefore, immediate and careful correction of blood potassium imbalances may prove to be a crucial approach in improving outcomes for these patients.